Outbreak investigation of Cholera in Shantinagar VDC of Ilam District in Eastern Nepal - Rayamajhi, RB; Pokharel, G; Sharma, G; Neupane, B; Khanal, VK; Kafle, SU; Paudel, IS; Pokharel, PK (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: In 2012 August, suspected cases of Cholera in increased number were reported to the district health office of Ilam by the in charge of Shantinagar health post asking for intervention to stop further occurrences. The aim of the investigation was to identify the possible source of infection, the causative agent and the application of local control measures for prevention of further recurrences. MATERIALS AND METHODS: Focus group discussion and Key informant survey were conducted to assess the sanitary hygiene and practices along with source of drinking water for probable cause of diarrhea. Similarly, face to face interview was done among the sick and healthy local residents to collect the demographic and clinical details. Ten stool and water samples were sent for analysis in Biratnagar, Dharan. RESULTS: 150 local residents had suffered from diarrhea with no deaths. People of all the age group were affected with children being more sufferers. Six of the stool analysis and eight of the water samples were positive for Vibrio Cholerae. It was also observed that sanitary hygiene and practices wasn’t adequate after nose and bottoms cleaning of the children and before preparing the meal. CONCLUSIONS: Lack of adequate cleanliness of the common water tank was found to be the culprit behind the incident and Vibrio Cholerae being the causative agent. Local residents and water management committee were demonstrated the technique of chlorination of water and proper hand washing practices to prevent further recurrences. DOI: http://dx.doi.org/10.3126/ijim.v2i3.8666 Int J Infect Microbiol 2013;2(3):87-90